2019
DOI: 10.1038/s41523-019-0125-7
|View full text |Cite
|
Sign up to set email alerts
|

Success rates of re-excision after positive margins for invasive lobular carcinoma of the breast

Abstract: Rates of positive margins after surgical resection of invasive lobular carcinoma (ILC) are high (ranging from 18 to 60%), yet the efficacy of re-excision lumpReceptor subtypeectomy for clearing positive margins is unknown. Concerns about the diffuse nature of ILC may drive increased rates of completion mastectomy to treat positive margins, thus lowering breast conservation rates. We therefore determined the success rate of re-excision lumpectomy in women with ILC and positive margins after surgical resection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Rates of BCS in early-stage ILC have increased by 11.6% from 1993 to 2003 [80], with accumulating evidence suggesting no significant long-term survival benefit for patients undergoing mastectomy [81,82]. Approximately 17% to 65% of patients with ILC require a second intervention, and re-excision lumpectomy is successful in achieving clear margins, particularly in those with node-negative disease [83,84]. The unique pathology of ILC leads to under-recognition of the extent of the disease in the breast on routine preoperative imaging and results in a more extensive surgery in order to obtain clear margins.…”
Section: Role Of Surgerymentioning
confidence: 99%
“…Rates of BCS in early-stage ILC have increased by 11.6% from 1993 to 2003 [80], with accumulating evidence suggesting no significant long-term survival benefit for patients undergoing mastectomy [81,82]. Approximately 17% to 65% of patients with ILC require a second intervention, and re-excision lumpectomy is successful in achieving clear margins, particularly in those with node-negative disease [83,84]. The unique pathology of ILC leads to under-recognition of the extent of the disease in the breast on routine preoperative imaging and results in a more extensive surgery in order to obtain clear margins.…”
Section: Role Of Surgerymentioning
confidence: 99%
“…As such, ILC is often difficult to detect via physical exam and mammography, resulting in a delayed diagnosis and more advanced disease at presentation. Additionally, ILC is associated with unique sites of metastasis [ 4 , 5 ] and more challenging surgical management [ 6 , 7 ]. Biomarkers for ILC are consistent with the hormone-dependent “luminal A” molecular subtype (e.g., estrogen receptor alpha (ERα, hereafter ER) and progesterone receptor positive, human epidermal growth factor receptor 2 (HER2) negative)) [ 1 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is likely due to the challenges in accurately assessing disease extent in ILC. A more recent study exploring the success of re-excision of positive margins in women with ILC reported that while initial positive margins occurred in 37.6% of cases, clear margins were achieved in 74.2% of patients who underwent a re-excision lumpectomy ( 62 ). This suggests improvements in the surgical management of ILC, and that completion mastectomies may not be required in patients who have positive margins following their initial breast-conserving surgery.…”
Section: Management and Treatment Of Ilcmentioning
confidence: 99%